Standard transthoracic echocardiography and transesophageal echocardiography views of mitral pathology that every surgeon should know - Tan, Timothy C. (Ann Cardiothorac Surg, 2015)
The mitral valve is the most commonly diseased heart valve and the prevalence of mitral valve disease increases proportionally with age. Echocardiography is the primary diagnostic imaging modality used in the assessment of patients with mitral valve disease. It is a noninvasive method which provides accurate anatomic and functional information regarding the mitral valve and can identify the mechanism of mitral valve pathology. This is especially useful as it may guide surgical repair. This is increasingly relevant given the growing trend of patients undergoing mitral valve repair. Collaboration between cardiac surgeons and echocardiographers is critical in the evaluation of mitral valve disease and for identification of complex valvular lesions that require advanced surgical skill to repair. This article will provide an overview of transthoracic and transesophageal assessment of common mitral valve pathology that aims to aid surgical decision making.